2006
DOI: 10.17221/3454-pse
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic response of chickpea (Cicer arietinum L.) cultivars to drought stress implemented at pre- and post-anthesis stages and its relations with nutrient uptake and efficiency

Abstract: Uptake of mineral nutrients in chickpea cultivars might be an important response in drought tolerance. An experiment under controlled conditions was carried out to study the genotypic response of 11 chickpea (Cicer arietinum L.) cultivars to drought and its relations with N, P, K, Ca, Mg, Fe, Zn, Mn and B uptake and uptake efficiency. Plants were grown either optimal or drought stress implemented at pre- (early drought stress, EDS) and post-anthesis (late drought stress, LDS) stages. Growth reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 15 publications
3
59
1
Order By: Relevance
“…According to Xia (1997), N, P, and K uptake decreased significantly under water stress in faba bean. In a study carried out with chickpea, 11 screened cultivars varied greatly with respect to nutrient uptake in both optimal and drought conditions (Gunes et al, 2006). They also reported that drought treatments significantly reduced nutrient uptakes and efficiencies of the cultivars and that the decrease in nutrient uptakes was more serious in late drought stress treatment than in early drought stress treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Xia (1997), N, P, and K uptake decreased significantly under water stress in faba bean. In a study carried out with chickpea, 11 screened cultivars varied greatly with respect to nutrient uptake in both optimal and drought conditions (Gunes et al, 2006). They also reported that drought treatments significantly reduced nutrient uptakes and efficiencies of the cultivars and that the decrease in nutrient uptakes was more serious in late drought stress treatment than in early drought stress treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the plant's nutrients, besides carbon, hydrogen, and oxygen, originate from the soil (Marschner, 1986). Drought is deleterious for plant growth, yield, and mineral uptake (Suther and Patel, 1992) and cultivars differ in their responses to environmental stress at different growth stages (Garg, 2003;Gunes et al, 2006). Under water-stressed conditions, there is a reduction in total nutrient uptake, followed by a reduction in mineral nutrient concentrations in crop plants, due to the decreased soil moisture (Baligar et al, 2001;Gunes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought stress alters many physiological and metabolic processes in plants ( Gunes et al, 2006). Shoot dry weight is one of the earliest plant responses to drought.…”
Section: Discussionmentioning
confidence: 99%
“…To tolerate many environmental stresses, plants set a plethora of adaptation mechanisms, from early responses to longer term metabolic and physiognomic alterations (Gunes et al, 2006). Water shortage stress is one of the most important abiotic stress factors which seriously limits plant growth and field crops production, more than any other environmental stresses.…”
Section: Introductionmentioning
confidence: 99%